Empowering language learners: Innovations in CEFR-based language learning applications - Amiruddin, Ahmad Zaki; Ghani, Mohammad Taufiq Abdul; Daud, Wan Ab Aziz Wan; Hussein, Nur Hafezah; Yamin, Nur Hazimah Mat; Abdullah, Yasmin See (Edelweiss Applied Science and Technology, 2025)
Language acquisition is crucial for fostering global relationships and promoting communication understanding in an increasingly globalized society. Technology has changed language learning, and the CEFR standardizes language proficiency evaluation. This article examines the need for CEFR-technology integration in language learning applications. The key difficulty is integrating CEFR-based frameworks with educational technology to produce effective language learning applications. This integration addresses varied learner competency levels and improves language acquisition. This study used a quantitative survey approach to examine CEFR-technology integration in language acquisition. Malaysian higher education students were recruited as the sample for this study. A structured questionnaire was the main data collection tool. This questionnaire used closed-ended questions to collect quantitative data on students' CEFR knowledge, language learning technology use, and CEFR-based application perceptions. Simple random sampling ensured a representative sample by giving each student an equal chance. Descriptive statistics were used to summarize the findings and assess the efficacy and use of the CEFR-based language learning tool. The results indicate that students were adept in basic technology skills but showed inconsistency in graphic design and multimedia editing. The high average scores in basic technology use suggest that students are comfortable with digital tools, while lower proficiency in more advanced applications indicates a need for further training. The study highlights the importance of integrating the Common European Framework of Reference for Languages (CEFR) with easy-to-use technologies in language learning. In conclusion, to enhance language education, it is crucial to provide professional development programs, design intuitive applications, and implement supportive policies. This approach can bridge proficiency gaps and ensure effective, engaging language learning experiences.